1987
DOI: 10.1080/15298668791385101
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Asbestos During Brake Maintenance of Automotive Vehicles by Different Methods

Abstract: Asbestos concentrations were measured during the different operations of brake maintenance of passenger cars, trucks and buses in 24 Finnish workplaces. The estimated average asbestos exposure during the workday (8-hr time-weighted average) was 0.1-0.2 fibers/cm3 during brake repair of trucks or buses, and under 0.05 f/cm3 during repair of passenger car brakes when the background concentration was not included in the calculations. The background concentration was estimated to be less than 0.1 f/cm3. During bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…With the introduction of bonded and pre-arced replacement brake shoes in the 1950s, the need for drilling, facing, and grinding during automobile brake repair was reduced substantially (Sheehy et al, 1989). However, there are limited reports of grinding of automobile brakes in foreign countries in the 1970s and 1980s (e.g., Jahn, 1983;Kauppinen and Korhonen, 1987;Cheng and O'Kelly, 1986;Ro¨delsperger et al, 1986), and it is therefore probable that grinding (and related activities) occurred to some degree in commercial garages in the US during the same time frame.…”
Section: Work Activities and Treatment/handling Of Brake Productsmentioning
confidence: 99%
“…With the introduction of bonded and pre-arced replacement brake shoes in the 1950s, the need for drilling, facing, and grinding during automobile brake repair was reduced substantially (Sheehy et al, 1989). However, there are limited reports of grinding of automobile brakes in foreign countries in the 1970s and 1980s (e.g., Jahn, 1983;Kauppinen and Korhonen, 1987;Cheng and O'Kelly, 1986;Ro¨delsperger et al, 1986), and it is therefore probable that grinding (and related activities) occurred to some degree in commercial garages in the US during the same time frame.…”
Section: Work Activities and Treatment/handling Of Brake Productsmentioning
confidence: 99%
“…For example, the mean short-term Abbreviation code represents specific cleaning, machining, or other activity (see Table 1). Kauppinen and Korhonen (1987) 4-33 P 30 1.5 (0.1-5.9) NA Machining GLE Y N Sampling duration reported as range and represents summary data (41 sample) Kauppinen and Korhonen (1987) 2-5 P 7 0.4 (0.1-0.9) NA Machining B Y N Sampling duration reported as range and represents summary data (41 sample) Kauppinen and Korhonen (1987) 5-6 P 1 0.5 NA Other CDD N N Not a specific activity Kauppinen and Korhonen (1987) 5-6 P 1 0.7 NA Other CDD N N Not a specific activity Kauppinen and Korhonen (1987) 3-26 P 6 0. Abbreviation code represents specific cleaning, machining, or other activity (see Table 1).…”
Section: Cleaning Methodsmentioning
confidence: 99%
“…A summary of the five government reports (Johnson et al, 1979;Roberts, 1980a, b;Roberts and Zumwalde, 1982;Sheehy et al, 1989) and ten published studies (Hatch, 1970;Knight and Hickish, 1970;Lorimer et al, 1976;Rohl et al, 1976;Jahn, 1983;Cheng and O'Kelly, 1986;Ro¨delsperger et al, 1986;Kauppinen and Korhonen, 1987;Plato et al, 1995;) identified as containing short-term asbestos air sampling data for brake mechanics is presented in Table 2. These 15 studies, conducted in the United States, United Kingdom, Finland, Germany, and Hong Kong between 1968 and 2000, represent more than 300 short-term personal asbestos air samples for automobile and truck mechanics collected during brake machining and cleaning activities.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reported measurements of asbestos fibers during the grinding of a new lining, before installation, were 2.7 and 4.8 fibers/cc 14) . Numerous studies have shown that the time-weighted average (TWA) airborne asbestos levels during brake lining repair or replacement on cars and trucks are consistently higher than the current OSHA PEL of 0.1 f/cc 15,16) . In 1971, the OSHA modified its permissible exposure limit (PEL) to eliminate the development of asbestosis, in which the 8-h concentration limits for occupational environment asbestos fiber were 12 fiber per milliliter (12 f/ml).…”
Section: Evaluation Of Asbestos Exposure During Brake Repair and Replmentioning
confidence: 99%